Aging monitoring and fault positioning for zinc oxide surge arresters based on the fifth harmonic of the leakage current - Lu, Yongling; Xue, Zhitong; Guo, Jiahao; Zhang, Chenyu; Liu, Jian; Xiao, Xiaolong; Sun, Jian (Frontiers in Physics, 2025)
Current techniques for aging monitoring and fault positioning for zinc oxide surge arresters usually use the third harmonic of the leakage resistive current. However, harmonic interference in the power grid voltage greatly affects the third harmonic, resulting in poor monitoring and positioning effects. Therefore, based on the harmonic characteristics of the resistive current, this article adopts the fifth harmonic of the leakage current as a novel monitoring indicator for zinc oxide surge arresters. In addition, it builds an aging experimental platform for zinc oxide surge arresters with voltage harmonic interference. An improved displacement current method and a fast Fourier transform algorithm are used to extract current harmonic features, and the percentage changes in features and harmonic sensitivity are introduced to analyze the fifth harmonic characteristics. A monitoring threshold and positioning scheme is proposed. The results show that the fifth harmonic exhibits high sensitivity to faults, with smaller changes in harmonic sensitivity and characteristic percentage, stronger resistance to harmonic interference. Furthermore, it is more suitable for aging monitoring and fault positioning for zinc oxide surge arresters than existing third harmonic analysis methods.